2022
DOI: 10.3389/fneur.2022.1026334
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sympathetic radiofrequency thermocoagulation in the treatment of cold hypersensitivity

Abstract: BackgroundCold hypersensitivity (CH) is a sensation of cold in the limbs and (or) body of a patient in an environment that is not considered cold by unaffected people, or a strong feeling of cold at a relatively low temperature. However, the currently available treatments are limited and often unsatisfactory. This study aimed to evaluate the clinical efficacy and safety of the sympathetic radiofrequency thermocoagulation (RF-TC) technique in patients with CH disorder.MethodsThe study is a retrospective analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…The patient was returned to the ward when vital signs were stable. Studies have shown [57][58][59] that CT-guided lower back sympathetic RF thermocoagulation has been gradually applied to the treatment of many autonomic nerve diseases, such as plantar hyperhidrosis (PH), cold hypersensitivity (CH), and diabetic peripheral neuropathy (DPN). Another study reported [60,61] that lumbar sympathetic radiofrequency thermocoagulation achieved a lasting effect in the treatment of CRPS, with a pain relief rate of 91.7% at three months and 83.3% at six months after treatment.…”
Section: Radiofrequency Thermocoagulation Of Thoracic Sympathetic Nervementioning
confidence: 99%
“…The patient was returned to the ward when vital signs were stable. Studies have shown [57][58][59] that CT-guided lower back sympathetic RF thermocoagulation has been gradually applied to the treatment of many autonomic nerve diseases, such as plantar hyperhidrosis (PH), cold hypersensitivity (CH), and diabetic peripheral neuropathy (DPN). Another study reported [60,61] that lumbar sympathetic radiofrequency thermocoagulation achieved a lasting effect in the treatment of CRPS, with a pain relief rate of 91.7% at three months and 83.3% at six months after treatment.…”
Section: Radiofrequency Thermocoagulation Of Thoracic Sympathetic Nervementioning
confidence: 99%